Connecting Gender, Age and Social Engagement - O' Donnell, Deirdre (Trinity College Dublin, 2007)
Social Structures and cultural norms have powerful prescriptive qualities. I have come to this project with the belief that both gender and age are simultaneously constructed by social and cultural structures, while paradoxically, they are embodied social 'realities'. In listening to the voices of older people narrating their own thoughts, memories and ideas I hope to gain insight into the complexities of their gendered subjectivities. I wish to discover how gender and ageing interact to affect social engagement in later life. I have narrowed my research lens to look at subjectivities situated within a specific location as they negotiate structural and embodied constraints. As a feminist, I believe that discursive knowledge concerning gender and age relations exists within social hierarchies of inequality. I therefore wish to access human agency within the language and experiences of older people. This study will address the relationship between social and cultural structures as well as embodied existence in a construction of gendered and aged identities. Finally, the creation of gender and aged selves will be linked to the reinforcement, resistance and appropriation of power within the context of social engagement.
Exhibited at the second Glucksman Memorial Symposium on June 13th 2007
Keywords: Gender Studies; Social construction of age; Social construction of gender